ACETYLCHOLINESTERASE INHIBITION AND ANTIOXIDANT ACTIVITY OF SOME MEDICINAL PLANTS FOR TREATING NEURO DEGENARATIVE DISEASE - Shahat, Abdelaaty Abdelaziz; Ibrahim, Abeer Y.; Ezzeldin, Essam; Alsaid, Mansour S. (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: Numerous plants in traditional practices of medicine have been used to treat cognitive disorders, including neurodegenerative diseases such as Alzheimer’s disease (AD) and other memory related disorders. Materials and Methods: We present here the evaluation of acetylcholinesterase (AChE) inhibitory and antioxidant activities of the aqueous methanol extracts of five traditional medicinal plants. Citrullus colocynthis, Emex spinosa, Rhazya stricta, Scrophularia hypericifolia and Caylusea hexagyna extracts were tested for their acetylcholinesterase inhibitory effect ant their antioxidant effect at different concentrations. Results: Citrullus colocynthis and Emex spinosa inhibited acetylthiocholinesterase at 400 µg/ ml by 83.54 and 81.92%. Emex spinosa and Scrophularia hypericifolia produced the maximum effect as DPPH radical scavenger (IC50= 10.89 and 11.88µg/ ml, respectively). Scrophularia hypericifolia showed the highest effect as superoxide radical scavenger (IC50= 20.83 µg/ ml)also it produced the highest ability to scavenge hydrogenperoxide radicals (IC50= 8.66 µg/ ml) while Emex spinosa and Caylusea hexagyna showed least IC50 for ferrous ion chelation (IC50≈15 µg/ ml) with powerful reduction capability. Conclusion:The determined antioxidant properties magnified the total antioxidant effect determined by ABTS assay that completely inhibited lipidperoxidation at 200 µg/ ml.